SEX DIFFERENCES IN THE TRAUMA-RELATED SYMPTOMS – A PILOT STUDY - Jerotić, Stefan; Marić Bojović, Nadja (Medicinski podmladak, 2016)
Introduction: During the year 2014, a part of the population from Serbia was exposed to floods. After natural disasters and other types of extreme trauma, some people will be more affected by trauma than others. How women and men differ, in the symptoms that can manifest after the exposure to extreme trauma, is still an open question. Aim: To evaluate if there are differences in the severity of trauma-related symptom clusters between the sexes (re-experiencing, avoidance, negative cognitions and mood, and arousal; according to DSM V) and in expiriencing negative emotional states (depression, anxiety, stress). Material and methods: Forty healthy volunteers from Obrenovac (25 women and 15 men) were administered with three instruments: The Life Events Checklist − LEC-5, PTSD checklist for DSM V – PCL-5 and Depression Anxiety Stress Scale − DASS. Results: The majority of subjects reported floods as the major lifetime trauma (72.5%). Despite the relatively low level of the post-traumatic symptom intensity (5.02 ±4.99), women exhibited significantly higher total post-traumatic symptom severity scores in comparison to men (p<0.01) and higher severity of trauma re-experiencing symptoms (p<0.01). Sex differences were neither observed in other trauma-related symptoms clusters, nor in the severity of current depression, anxiety and stress symptoms. Conclusion: In the non-clinical sample, with only a sub-threshold level of post-traumatic symptoms, the most prominent difference between sexes was found in relation to re-experiencing and this finding is consistent with the results obtained from clinical samples. Future studies are needed, in order to examine whether trauma-focused treatments can be gender-tailored and to which extent they might prevent the full-blown post-traumatic stress disorder. Keywords: posttraumatic stress disorder, trauma, sex differences, depression, floods